P81 Non-malignant resections for suspected malignancy: do they really represent benign disease?. (December 2018) - Frost, F; Page, R; Walshaw, MJ; Ledson, MJ
Abstract : Introduction: To optimise the definitive management of early-stage lung cancer, indeterminate pulmonary nodules are often resected without a prior tissue diagnosis and a proportion of resections will therefore yield benign pathology. We investigated the rates and outcomes of non-malignant resections at our centre in the last decade. Method: We reviewed all 1328 resections for suspected primary lung malignancy where there was no pre-operative tissue diagnosis carried out at our centre between 2007 and 2017, looking at any differences in clinical characteristics between those patients who had benign and malignant lesions as well as the post-operative outcome. Results: Histopathology demonstrated benign nodules in 126/1328 (9.5%): this cohort was younger (64.5±9.6 years vs 68.8±9.6 years, p<0.001) and had less obstructed spirometry, but similar smoking status and dyspnoea scores as those with malignancy (table 1). Most common benign diagnoses were organising pneumonia (24, 19.0%), non-specific granulomatous inflammation (18, 14.3%) and tuberculosis (13, 10.3%). There was no difference in perioperative mortality (1.6% vs 2.1%, p=0.97 for benign and malignant groups respectively). As expected, 5 year mortality was high in the malignant group (49.3%), but although significantly less (p<0.001), 20.4% of the benign cohort had still deceased in this period. Conclusions: This is one of the largest series looking at resection of indeterminate pulmonary nodules. Although resection of benign nodules may be considered unhelpful, the fact that one fifth of patients had deceased at 5 years suggest that they represented active non-malignant disease rather than incidental findings.